PENGARUH VARIASI LEBAR CFRP PADA BAGIAN TARIK TERHADAP DAKTILITAS BALOK BETON BERTULANG PASKA PERBAIKAN - Atika Ulfah Jamal; Novi Rahmayanti; Helmy Akbar Bale; Iqbal Haqiqi (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2016)
Retrofitting should be done on reinforced concrete beams were damaged the structure, it is to restore or improve the strength and ductility. One of the innovations of materials that can be used for retrofitting is Carbon Fiber Reinforced Polymer (CFRP). The width of the CFRP used for retrofitting an effect on load and deflection occurs in the beam, it will also affect the ductility of the beam. In this study examined the influence of the width of CFRP for retrofitting to the ductility of reinforced concrete beams with dimensions of 15x20x120 cm3. The beam is loaded until cracking occurred. Retrofitting performed on beams that have been fractured by adding CFRP on the tensile reinforcement of reinforced concrete beams. The wide variationCFRP is used to repair the beam, which is 5 cm, 10 cm, and 15 cm. The results showed that the width of CFRP placed on the tensile reinforcement in reinforced concrete beam elements repair after damage affects the curvature ductility. The wider the CFRP used for the retrofit of reinforced concrete beams lead to the greater percentage decrease in ductility curvature.